2006
DOI: 10.1038/sj.bjc.6603063
|View full text |Cite
|
Sign up to set email alerts
|

Co expression of SCF and KIT in gastrointestinal stromal tumours (GISTs) suggests an autocrine/paracrine mechanism

Abstract: KIT is a tyrosine kinase receptor expressed by several tumours, which has for specific ligand the stem cell factor (SCF). KIT is the main oncogene in gastrointestinal stromal tumours (GISTs), and gain-of-function KIT mutations are present in 70% of these tumours. The aim of the study was to measure and investigate the mechanisms of KIT activation in 80 KIT-positive GIST patients. KIT activation was quantified by detecting phosphotyrosine residues in Western blotting. SCF production was determined by reverse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 31 publications
4
34
0
1
Order By: Relevance
“…Interestingly, we observed that the KIT inhibitor imatinib partially relieved this blockade and restored KIT expression at the cell surface, suggesting that the constitutional activation of mutated KIT is responsible for the intracellular retention of the protein. Moreover, we previously showed that SCF was detectable in most GISTs, and might therefore contribute to its activation (48). Several tyrosine kinase inhibitors are currently used to treat patients with cancer, and belong to two main types: antibodies directed against surface receptors and small specific inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we observed that the KIT inhibitor imatinib partially relieved this blockade and restored KIT expression at the cell surface, suggesting that the constitutional activation of mutated KIT is responsible for the intracellular retention of the protein. Moreover, we previously showed that SCF was detectable in most GISTs, and might therefore contribute to its activation (48). Several tyrosine kinase inhibitors are currently used to treat patients with cancer, and belong to two main types: antibodies directed against surface receptors and small specific inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Only 5 of 32 cases (16%) showed coexpression of KIT and SCF. Interestingly, however, autocrine/paracrine stimulation is postulated to be one of the mechanisms by which KIT activation occurs in GISTs, 42 small cell lung carcinomas 43 and gliomas, 44 and autocrine stimulation maybe responsible for KIT activation in these five cases of Merkel cell carcinoma that are KIT þ /SCF þ.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that other vascular cytokines may play a role in this disease. Recently, most GISTs have been shown to express the ligand for Kit, stem cell factor (26). Stem cell factor may play an important role in GIST progression and imatinib efficacy in lieu or in combination with VEGF.…”
Section: Discussionmentioning
confidence: 99%